2012
DOI: 10.1515/ijdhd-2012-0049
|View full text |Cite
|
Sign up to set email alerts
|

Environmental smoke exposure associated with increased prevalence of dental caries in low-income children

Abstract: Dental caries are of serious concern as increasing numbers of cases of early childhood caries are seen. Oral hygiene and the development of dental caries is a challenging issue to address in any child. However, children in lower socioeconomic groups are disproportionately affected when compared with their higher-income peers. Low-income children are found to be twice as likely to have dental problems, with a reported prevalence of up to 50 % . Several environmental factors have been found to play a role in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Jakhete and Gitterman[ 47 ] found that exposure to tobacco use and poor nutrition were associated with higher caries prevalence in children from a low socio-economic level. Delpisheh[ 48 ] confirmed that passive exposure to tobacco use in children is significantly associated with low socio-economic level.…”
Section: Discussionmentioning
confidence: 99%
“…Jakhete and Gitterman[ 47 ] found that exposure to tobacco use and poor nutrition were associated with higher caries prevalence in children from a low socio-economic level. Delpisheh[ 48 ] confirmed that passive exposure to tobacco use in children is significantly associated with low socio-economic level.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed (table-7) increased DMF score of 13.1+/-0.71 in parents with low income followed by mean DMF score 7.35+/-4.07 in parents with medium income and mean DMF score of 3.24+/-3.97 in high income parents, which indicated a negative correlation between DMF score and socioeconomic status of the parents. Jakhete and Gitterman 28 have also stated that exposure to tobacco use were associated with higher caries prevalence in children from a low socio-economic level. Delpisheh 29 confirmed that passive exposure to tobacco use in children is significantly associated with low socio-economic level.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to these etiological evidences, there are grounds to assume that the association between prenatal smoking and caries in children is mainly due to socioeconomic factors. Generally, children with lower living standards exhibit higher caries rates [29][30][31]. It should be noted that post-partum smoking or household smoking has also been shown to be a possible predictor of dental caries in offspring since children would involuntarily inhale tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…These completely opposite results may be caused by various possible confounders because existing evidences suggest multiple factors like socioeconomic status, involuntary smoking, breastfeeding and its duration, maternal educational level and mode of delivery will affect the development of dental caries in children [19,[24][25][26][27][28]. Some studies have shown that children born in smoking households may be raised in a low socioeconomic level with insufficient nutrition [29] and have poorer oral hygiene with lower frequency of tooth brushing and more sugar intake [30,31], which are conducive to the occurrence of dental caries.…”
Section: Introductionmentioning
confidence: 99%